Preventive Healthcare System and Religious Rites of Burial During Pandemic: A Comparison between Jewish and Islamic Rituals - Abdulrahman Obeid Hussein; Islam, Tazul; Adnan Mohd Shalash (Maʿālim al-Qurʾān wa al-Sunnah, 2023)
Many funeral guidelines and regulations were imposed during the COVID-19 restriction movement to control the risk of Corona spreading, such as maintaining social distance and indoor and outdoor safe gatherings. Due to the high risk of contagion, some religious rites were avoided, like the gathering of many comforters, taking the farewell look at the deceased, and almost cancelling the decrees of religious burial and grief, which are spiritual remedies for those who lost their loved ones. Since both Judaism and Islam forbid cremation, the burial rites should be strictly monitored, and the decision to hold a modified mourning tribute for the deceased must be taken cautiously and in cooperation with the competent medical authority. But how does the new funeral regulation coincide with religious values? And how could Jewish and Islamic traditions about washing the infected deceased’s body, burial shroud, coffin, cemetery, initial mourning period, and other customs be preventive healthcare instructions? This article is attempting to answer these questions in light of Biblical and Quranic teachings.